A Level of Student Self-Discipline in E-Learning During Pandemic Covid-19 - Siti Nurajrina Binti Muksin; Mardzelah Binti Makhsin (Procedia of Social Sciences and Humanities, 2021)
Self-discipline in academics is the firmness of students in training themselves to be better in their learning. E-learning is now a growing learning method in every corner of the globe. It is able to speed up teaching and make the learning process last a lifetime. In Malaysia, the effectiveness of e-learning among school students may differ from IPT students where e-learning has a positive impact on IPT students. It was found that not many studies have been done on high school students related to distance education using e-learning methods. This quantitative descriptive study was conducted to find out the level of self-discipline of secondary school students in the world of e-learning during the period of the Covid-19 Movement Control Order in Malaysia as well as its relationship with gender and academic performance. The sample of this study was randomly selected consisting of 165 respondents of upper secondary students in Form Four and Five at SMK Syed Sirajuddin, Perlis. To achieve the objectives of this study, a questionnaire was used to collect research information and data was analysed with the help of Statistical Packages for Social Science (SPSS version 26). Overall, the results of the mean calculation found that the level of self- discipline of students is at a moderate level. The results of the t-test found out that there was no significant difference between the levels of students’ self-discipline based on gender. Meanwhile, Pearson correlation test proves that students' level of self-discipline also affects their academic performance. At the end of this writing, some suggestions have been put forward. Finally, this study has an impact not only on the world of education where teaching and learning are in new norms but also on the world of information technology to further develop interactive learning.